IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN EKONOMI - Muliansyah, Sandra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The study aims to find out the Implementation of Curriculum 2013 On Economic Subjects in SMA Negeri 01 Sandai Ketapang District. This research is a type of descriptive evaluative research. The subject of this research is the subject of economics teacher. Data analysis techniques in this study using descriptive analysis. In this study, data were collected through observation and interview methods. The results show that, overall, the Implementation of Curriculum 2013 on Economic Subjects at SMA Negeri 01 Sandai Ketapang District runs in accordance with the basic concepts and principles of the Curriculum 2013. But on the other hand there are some problems that arise from the implementation of the 2013 curriculum. From The results of interviews and observations made by researchers on economic subjects teachers, can be concluded when the process of teaching teachers can implement or implement the Curriculum 2013 on economic subjects as well. Keyword :Implementation, Curriculum 2013, Economic Subject.